2021
DOI: 10.7717/peerj.11018
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of immune-related long noncoding RNAs as diagnostic biomarkers in psoriasis

Abstract: Background Psoriasis is a chronic immune-mediated inflammatory dermatosis. Long noncoding RNAs (lncRNAs) play an important role in immune-related diseases. This study aimed to identify potential immune-related lncRNA biomarkers for psoriasis. Methods We screened differentially expressed immune-related lncRNAs biomarkers using GSE13355 (skin biopsy samples of 180 cases) from Gene Expression Omnibus (GEO). Moreover, Gene Ontology (GO) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…POC1B-AS1 is also a risk factor in the prognostic model of endometrial carcinoma ( Liu J. et al, 2021 ). In psoriasis, CCDC18-AS1, regarded as immune-related lncRNA, can be a potential diagnostic biomarker ( Fan et al, 2021 ). THUMPD3-AS1 can regulate self-renewal by ceRNA network of miR-543 and ONECUT2 associated with non-small cell lung cancer ( Hu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…POC1B-AS1 is also a risk factor in the prognostic model of endometrial carcinoma ( Liu J. et al, 2021 ). In psoriasis, CCDC18-AS1, regarded as immune-related lncRNA, can be a potential diagnostic biomarker ( Fan et al, 2021 ). THUMPD3-AS1 can regulate self-renewal by ceRNA network of miR-543 and ONECUT2 associated with non-small cell lung cancer ( Hu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 Taken together, we believe that the GADPH-LINC01116 axis plays a positive role in lung cancer and more biochemistry experiments are needed to test this idea. LINC01137 was previously found to be an immunerelated biomarker in the diagnosis of psoriasis and also an indicator for chemical stress response 31,32 and the upregulation of it may result in poor overall survival. MLST8 (MTOR Associated Protein, LST8 Homolog) is an essential part of the mTORC1 pathway and has the ability to enhance the mTOR kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In DMD, the immune system is activated and several types of immune cells, such as CD4+ and CD8+ T cells, Tregs, and NK cells, invade the skeletal muscles [16]. A recent study showed that lncRNA CCDC18-AS1 is positively correlated with activated myeloid dendritic cells and neutrophils [52], in concordance with our results that showed that the expression of lncRNA CCDC18-AS1 was positively correlated with the proportion of activated NK cells, neutrophils, and Tregs but negatively correlated with resting myeloid dendritic cells and M2 macrophages. Our study also showed that the proportions of Tregs, activated NK cells, neutrophils, M2 macrophages, and resting myeloid dendritic cells were signifcantly diferent between patients with DMD and normal control individuals.…”
Section: Discussionmentioning
confidence: 99%